Estudio del proceso de extrusión del latón al bismuto y su maquinabilidad - Dionicio Padilla, Eusebio (2011)
The current study has determined that the materials from brass to bismuth, 1.11%, 1.46% and 2.48% respectively, have the following characteristics: the brass to bismuth material drawing, uniform round bar of 19 mm which microstructure is formed by α + β, shows inclusions of bismuth in the grain limits and in the same grain. The grain deformation is smaller on the surface, and it becomes bigger as it reaches the center. The mechanical properties of the 19 mm drawing material, I and II are bigger than the established by the ASTM B 16/B 16M, being the HRB hardness higher than the established by the norm. Also the material is wrought to obtain pieces for gas valves. The machinability index of the brass’s drawing materials that contains bismuth between 1.0 and 2.5% should be in a range from 85 and 90